ALIRAN MODAL ASING, PERTUMBUHAN EKONOMI DAN INDIKATOR MAKROEKONOMI INDONESIA PASCAKRISIS ASIA - , JUJU MELANIE, Muhammad Edhie Purnawan, M.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research is to analyze the response of real economic growth and other macroeconomic indicators such as nominal exchange rate, the narrow money supply, inflation, and current account balance toward shock on capital flows. In addition, this study tries to analyze the contribution of capital flows in explaining the variability in the macroeconomic indicators. Research is done using SVAR with theoretical restriction which was formed in lower triangular matrix. The datas which are used are quarterly with observational data 2000:1 to 2011:4. Capital flows are classified by the type of investment into net foreign direct investment and net portfolio investment (further classified by the types of instruments into debt and equity) that are percentaged to GDP. Research shows that the growth effect of capital flows depend on the type of investment. The result of impulse response functions and forecast error variance decompositions, show that the percentage of net portfolio investment in the form of debt and net foreign direct investment to GDP give great growth effects, while the percentage of net portfolio investment in the form of equity to GDP does not. Impulse response functions show that the rising shock in all types of capital flows appreciating nominal exchange rate and worsenning the current account. A rising shock in the percentage of net foreign direct investment and net portfolio investment in the form of debt to GDP, increase the money supply, whereas this response is obtained only in the first period of a rising shock in the percentage of net portfolio investment in the form of equity to GDP. The response of inflation is negative, instantaneous, and the temporary after a rising shock in the percentage of of net foreign direct investment to GDP, and positive for a rising shock in the percentage of net portfolio investment to GDP. Forecast error variance decompositions show that the three types of capital flows are high enough in explaining the variability of the nominal exchange rate and the current account. Percentage of net foreign direct investment and net portfolio investment in the form of debt to GDP ratio has a fairly high contribution in explaining the variability of inflation and the money supply, whereas contribution of the percentage of net portfolio investment in the form of equity to GDP is very low.